Pembangunan Sistem Informasi Manajemen Cuti Karyawan Berbasis Web Pada Pt Sarana Kreasindo Teknologi - Restu Fauzi Lesmana; Lita Lestrai Utami (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2024)
An employee is someone who works or has worker status in an organization, company orgovernment agency. This individual has the responsibility to carry out the duties and obligations that havebeen determined by the rules and policies that apply in the workplace. Meanwhile, leave is a period of timewhere an employee is given permission not to come to work for a certain period of time. Providing leave is aprivilege given to employees as part of company policy or applicable employment regulations. The researchmethod used to create a web-based leave application system with research method that can be used is thesystem development method. This method involves steps such as requirements analysis, system design,implementation, testing, and evaluation. With research inti the development of a web based leave managementrecorded in a systematic and perfectly monitored manner in a database.